Sustainable Membrane Technology for Water and Wastewater Treatment - Figoli, Alberto; Criscuoli, Alessandra; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book analyses the sustainability of membrane operations applied on an industrial scale, as well as that of those under investigation on lab/pilot scales, covering also the preparation of both polymeric and inorganic membranes. It presents reverse osmosis in desalination, membrane bioreactors for municipal wastewater treatment and pressure-driven industrial wastewater treatment in agrofood and textile fields as examples of industrial membrane operations. Regarding the membrane processes still on a lab/pilot scale, the analysis includes membrane operations for the recovery of valuable products from wastewater streams, for the removal of toxic compounds from water/wastewater, and for zero liquid discharge approaches in desalination. The book offers a useful guide for scientists and engineers working in various fields, including membrane technology, separation, desalination, and wastewater treatment. Alberto Figoli and Alessandra Criscuoli are both Senior Researchersat the Institute on Membrane Technology (ITM-CNR), Italy.
Keywords: Chemistry, Technical; Pollution; Biophysics; Water; Hydrology; Industrial Chemistry; Pollution; Biophysics; Water